Optimalisasi Kemampuan Analisis Teks Argumentasi Melalui Model Think Pair Share di SMK Negeri 6 Surabaya - Saadah, Ayu Ummatus; Supartini, Titin; Suhartini, Ratna; Buditjahjanto, I Gusti Putu Asto; Anifah, Lilik (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
This study aims to examine the effect of the Think Pair Share (TPS) learning model on improving students’ learning outcomes in analyzing argumentative texts. A qualitative approach using Classroom Action Research (CAR) was conducted in two cycles. The subjects of the study were eleventh-grade students at SMKN 6 Surabaya. Each cycle included planning, implementation, observation, and reflection stages aimed at continuously improving the learning process. The results indicate that implementing the TPS model significantly increased students’ active participation and learning achievement. In the first cycle, the average student score was 71.2 with a completeness rate of 65.6%. After revising the learning strategy in the second cycle, the average score increased to 81.6 with a completeness rate of 87.5%. The TPS model proved effective in creating a collaborative, interactive, and student-centered learning environment. Through three main stages—think (individual thinking), pair (discussion in pairs), and share (sharing within groups)—students became more actively involved, developed critical thinking skills, and were able to express their opinions openly and effectively. These findings suggest that the TPS model is an effective and viable alternative learning strategy to enhance student engagement, comprehension, and academic performance. Therefore, this study recommends that teachers consistently implement the TPS model to improve the quality of learning processes and student outcomes, particularly in teaching argumentative text analysis.